2019
DOI: 10.36526/kejaora.v4i2.705
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Status Gizi Dengan Kebugaran Jasmani Siswa-Siswi SMP Negeri 1 Ambon

Abstract: Penelitian ini bertujuan untuk mengetahui hubungan status gizi dengan kebugaran jasmani siswa-siswi SMP Negeri 1 Ambon. Penelitian ini merupakan jenis Penelitian deskriptif korelasional dan survei dengan menghubungkan variabel terikat dengan variabel bebas yaitu status gizi dengan tingkat kebugaran jasmani. Subjek dalam penelitian ini adalah siswa-siswi dengan berbagai status gizi yang berjumlah 28 orang. Berdasarkan uji hipotesis, maka hasil penelitian ini menunjukkan bahwa ada hubungan status gizi deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to Hukubun & Souisa (2019) good and regular nutrition has a positive impact on a person's fitness level. The findings of this study indicate that factors other than exercise also contribute to physical fitness, as explained in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hukubun & Souisa (2019) good and regular nutrition has a positive impact on a person's fitness level. The findings of this study indicate that factors other than exercise also contribute to physical fitness, as explained in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Optimizing children's growth can be achieved by physical exercise adjusted to the age level of children, including 7-8 years (grade 1-2), 9 years (grade 3), 10-11 years (grade 4-5), and 12-13 years (grade 6) [18]. Result of a study conducted before the COVID-19 outbreak found that there was a significant relationship between nutritional status, physical activity, and physical fitness level of Al-Hikmah Gempolmanis elementary school students in Indonesia [19]. A study of stunted children aged 6-15 years in Peru suggested that stunting affects the fitness level of stunted children [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors can influence stunting. However, the coronavirus disease 2019 (COVID- 19) outbreak might be one obstacle for families infected by the virus to deal with stunting [4]. Stunting has become an indicator of the nutritional issue in children due to inadequate intake of nutrients for a long time or accompanied by recurrent infectious disease.…”
Section: Introductionmentioning
confidence: 99%